AN EXPLANATIVE STUDY ON THE MODULE FOR SUPERVISING AND ASSESSING EDUCATION STAFF PERFORMANCE AT PRINCIPAL EMPOWERMENT TRAINING: - - Supriyana, Heri (Advances in Social Sciences Research Journal, 2020)
AN EXPLANATIVE STUDY ON THE MODULE FOR SUPERVISING AND ASSESSING EDUCATION STAFF PERFORMANCE AT PRINCIPAL EMPOWERMENT TRAINING ABSTRACT Heri Supriyana Institute for Development and Empowerment of Principals and Supervisors heri_s_p@yahoo.com The result of 2015 principal competency test shows that most of principals have not sufficient principal competency so that they have not been able to carry out their main tasks and functions properly. Likewise, the most of principals who have been appointed as principals do not yet have a Certificate of principal training, so that the most of principals do not meet the requirements to become principals. Based on this problem the Ministry of Education and Culture conducts training for strengthening principals with certain modules. The Directorate General of Teachers and Educational Personnel has written a training module for strengthening principals. These modules include the supervision module and the performance assessment of the education staff written by the author. The module has not been tested for relevance, adequacy, consistency, and sequences. In order to obtain a module for supervision and the performance assessment of teaching staff that is ready to be used in education and training, this study was conducted. The purpose of this study was to determine the level of relevance, adequacy, consistency, and sequences of the supervision module and the assessment of the performance of the education staff in the training of strengthening principals. This research is an explanative research. The data collection method uses closed questionnaire and open questionnaire techniques. The results of this study are the relevance aspects of getting a score of 3.73 (good enough), the adequacy aspect of getting a score of 3.64 (good enough), the consistency aspect of getting a score of 3.74 (good enough), the aspect of sequencing getting a score of 3.86 (good enough). Besides that from the systematic aspect of writing the category of statement "quite systematic" has the largest percentage of 77.10%, the aspect of appearance / graphic design of the category of statement "quite good" has the largest percentage of 74.23%, on the aspect of content / content category of statement "enough complete and detailed "has the largest percentage of 78.58%. The conclusion of this research is that the supervision module and the performance assessment of the education staff in the sc principal strengthening training program are good enough to be used in the principal strengthening training because they are relevant, sufficient content, consistent enough and inter-material enough sequences. Keywords: explanatory study; module; supervision; performance assessment; educational staff.